Antimicrobial efficacy of eucalyptus essential oil (Eucalyptus spp) on Escherichia coli and Staphylococcus aureus subsp. aureus strains - Montero-Recalde, Mayra (2019)
The objective of this study was to evaluate the in vitro antimicrobial effect of eucalyptus essential oil (Eucaliptus spp) on Escherichia coli ATCC® 11229 and Staphylococcus aureus subsp. aureus ATCC® 25904. Concentrations of 30, 60 and 90% were evaluated in dilution in 96.8% ethanol. The Minimum Inhibitory Concentration (MIC) was determined by the broth microdilution method. The bacterial inoculum was standardized to 0.5 of the MacFarland scale in spectrophotometer, obtaining as a result that the concentrations of 60 and 90% did not present turbidity. The Minimum Bactericidal Concentration (MBC) determined in Mueller-Hinton agar was present from the 60% concentration for the two strains under study. The antimicrobial susceptibility test indicated that all concentrations showed antimicrobial sensitivity and that the concentrations at 30 and 60% were not significantly different, presenting halos of inhibition of 10.25 mm and 10.65 mm in the concentration of 30% for the strains of Escherichia coli and Staphylococcus. aureus subsp. aureus, respectively. On the other hand, the results for the strain S. aureus subsp. aureus showed that concentrations at 60% and 90% formed larger diameter halos than the E. coli strain.